Harmful R-loops are prevented via different cell cycle-specific mechanisms - Marta San Martin-Alonso (Nature Portfolio, 2021)
Different factors protect cells from harmful R-loops, but the way these are formed is still unclear. Authors show here that R-loops form co-transcriptionally by different manners and cells possess specialized mechanisms to prevent them in each case, a major mechanism being independent of replication and another one being linked to replication.